Towards personalised software in machine design - Pokojski, Jerzy (Computer Assisted Methods in Engineering and Science, 2002)
The paper presents a concept of knowledge based software supporting a long period machine design analysis - intelligent personal assistant. The concept of intelligent personal assistant is based on the maze model and optimisation model of the design process. The functional structure of the whole system is shown.